Microstructure and mechanical properties of an oxide-dispersed ultrafine-grained maraging steel - Bowen Shi; Tianyi Zeng; Nairong Tao; Xianbo Shi; Jiarong Zhang; Wei Wang; Sybrand van der Zwaag; Yiyin Shan; Wei Yan (Journal of Materials Research and Technology, 2025)
A novel oxide-dispersed strengthened T250 maraging steel (ODS-T250 steel) was prepared by mechanical ball milling followed by hot isostatic pressing. Martensitic transformation behavior, ultrafine-grained martensite microstructure and tensile properties of the ODS-T250 steel were compared to its oxide-free counterpart (T250 steel). The results indicated that ODS-T250 steel exhibited excellent microstructural thermal stability, maintaining an effective grain size of 0.348 μm even after quenching from 1200 °C, whereas T250 steel exhibited a much larger grain size of 5.473 μm. After quenching, the ODS-T250 steel showed significantly distinct variant selectivity, and its martensite morphology was unprecedented equiaxed structure rather than typical lath-type. Statistical analysis revealed that there was only a single variant formed when the prior austenite grain size (PAGS) was below 0.43 μm. Moreover, the martensite start (Ms) temperature of ODS-T250 steel was lower than the T250 steel due to its ultrafine PAGS and the dispersed oxide particles. The refinement of PAGS and the presence of oxide particles led to a simultaneous improvement in both strength and ductility of ODS-T250 steel.